PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE HOLLYWOOD SQUARES REVIEW TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS VIII SMP NEGERI 11 PADANG - Nurmayunita, Anita; Husna, Dra.Hj.; Cesaria, Anna (Pendidikan Matematika, 2014)
Â This research is motivated by the lack capability of mathematical communication students as well as students are less interested in learning mathematics. This study aims to determine whether students capability of mathematical communication by applying hollywood squares review strategies better than the students capability of mathematical communication by applying conventional learning in class VIII SMP Negeri 11 Padang school year 2013/2014. This was an experimental research and applied random research toward the subject. Based on the perceived data analysis, the class sample has normally distributed and homogeneous. Data analysis techniques are used to test the hypothesis is not a party with the help of MINITAB software. Hypothesis test results obtained P-value= 0.000 is less than Î±= 0.05, then reject H0, so the hypothesis in this study received. It can be concluded that the capability of mathematical communication students with hollywood squares review strategies better than the students capability of mathematical communication by applying conventional learning in class VIII SMP Negeri 11 Padang school year 2013/2014.